2009
DOI: 10.1578/am.35.2.2009.253
|View full text |Cite
|
Sign up to set email alerts
|

Blood Chemistry of Antillean Manatees (<I>Trichechus manatus manatus</I>): Age Variations

Abstract: The Antillean manatee (Trichechus manatus manatus) is the most endangered aquatic mammal in Brazil. Sampling blood data from such critically endangered marine mammal species is extremely challenging. Although several hematological studies have been developed for captive manatees, captivity studies addressing the environmental and physiological effects on blood values are scarce. The present work describes blood biochemistry values for captive Antillean manatee adults and calves and verifies the occurrence of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Both African and Asian elephants ( Elephas Maximus ) have very low serum uric acid levels of 0.2 and 0.22 mg/dl, respectively ( 110 , 111 ). West Indian manatees ( Trichechus manatus ) have serum uric acid levels of 0.97 mg/dl for adult and 0.71 mg/dl for calves ( 112 ), which is similar to 1.1 mg/dl observed in the related Amazonian manatee ( Trichechus inunguis ) ( 113 ). Thus, while the loss of this pathway in human and knockout mice is associated with high serum uric acid levels, elephants and manatees have levels that are lower or comparable to the level observed in wild-type mice.…”
Section: Resultssupporting
confidence: 56%
“…Both African and Asian elephants ( Elephas Maximus ) have very low serum uric acid levels of 0.2 and 0.22 mg/dl, respectively ( 110 , 111 ). West Indian manatees ( Trichechus manatus ) have serum uric acid levels of 0.97 mg/dl for adult and 0.71 mg/dl for calves ( 112 ), which is similar to 1.1 mg/dl observed in the related Amazonian manatee ( Trichechus inunguis ) ( 113 ). Thus, while the loss of this pathway in human and knockout mice is associated with high serum uric acid levels, elephants and manatees have levels that are lower or comparable to the level observed in wild-type mice.…”
Section: Resultssupporting
confidence: 56%
“…However, blood reference ranges or values can di er among populations of the same species and vary according to age, sex, diet, environment, physiological conditions, and activity level. e hematology and blood chemistry of various Antillean manatee populations have been documented for Guyana [7], Mexico [8], Belize [9,10], Brazil [11][12][13][14], and for the Florida subspecies (T. manatus latirostris) [6,[15][16][17][18][19][20][21][22][23][24][25]. However, this has not been ascertained for Antillean manatees inhabiting the Greater Antilles.…”
Section: Introductionmentioning
confidence: 99%
“…The most important subject was 'ecology' (24.5%), which includes a relatively large amount of preliminary, lowbudget assessments of manatee occurrence, distribution, and conservation status in particular territories/countries (e.g., Castelblanco-Martínez et al, 2009;Gonzalez-Socoloske et al, 2011;Arévalo-González et al, 2014). Another relevant category is 'Conservation' (16.6%), which includes quantitative or qualitative descriptions of threats to manatee viability/health such as boat collisions (e.g., Borges et al, 2007), poaching (e.g., Jiménez-Pérez, 2002), contaminants (e.g., Anzolin et al, 2012; Romero-Calderón et 1980-1982 1983-1987 1988-1992 1993-1997 1998-2002 2003-2007 2008 1980-1982 1983-1987 1988-1992 1993-1997 1998-2002 2003-2007 2008 (e.g., Vanoye, 2002;Silva et al, 2009;Takeuchi et al, 2016). In the topic behavior (10.3%), papers approaching aspects on manatee communication (e.g., Alicca et al, 1997;Sousa-Lima et al, 2008;Umeed et al, 2018;Merchan et al, 2019;Ramos et al, 2020), learning and welfare (e.g., Hénaut et al, 2020), husbandry (Lima et al, 2005), circadian rhythm (Holguin-Medina et al, 2015), habitat preferences (e.g., Ramírez-Jiménez et al, 2017), and movements and migrations (e.g., Castelblanco-Martínez et al, 2013) were found.…”
Section: Resultsmentioning
confidence: 99%